A Molecular Survey of Anaplasma spp., Rickettsia spp., Ehrlichia canis and Babesia microti in Foxes and Fleas from Sicily. (November 2013) - Torina, A.; Blanda, V.; Antoci, F.; Scimeca, S.; D'Agostino, R.; Scariano, E.; Piazza, A.; Galluzzo, P.; Giudice, E.; Caracappa, S.
Summary: Fleas (Insecta: Siphonaptera) are obligate bloodsucking insects, which parasitize birds and mammals, and are distributed throughout the world. Several species have been implicated in pathogen transmission. This study aimed to monitor red foxes and the fleas isolated from them in the Palermo and Ragusa provinces of Sicily, Italy, as these organisms are potential reservoirs and vectors of pathogens. Thirteen foxes ( Vulpes vulpes ) and 110 fleas were analysed by polymerase chain reaction (PCR) to detect DNA of the pathogens Ehrlichia canis, Babesia microti, Rickettsia spp., Anaplasma phagocytophilum, Anaplasma platys, Anaplasma marginale and Anaplasma ovis . In the foxes, A. ovis was detected in only one animal, whereas the prevalence of the E. canis pathogen was 31%. B. microti and Rickettsia spp. were not detected. Of all of the collected fleas, 75 belonged to the species Xenopsylla cheopis, 32 belonged to Ctenocephalides canis, two belonged to Ctenocephalides felis and one belonged to Cediopsylla inaequalis . In the fleas, the following pathogens were found: A. ovis (prevalence 25%), A. marginale (1%), A. phagocytophilum (1%), Rickettsia felis (2%) and E. canis (3%). X. cheopis was the flea species most frequently infected with Anaplasma, in particular A. ovis (33%), A. marginale (1%) and A. phagocytophilum (1%). Both C. felis exemplars were positive for R. felis . E. canis was found in the lone C. inaequalis and also in 3% of the X. cheopis specimens. No fleas were positive for B. microti or A. platys . As foxes often live in proximity to domestic areas, they may constitute potential reservoirs for human and animal parasites. Further studies should be performed on fleas to determine their vectorial capacity.